Geneologis Nilai-Nilai Islam dalam Pancasila dan UUD 1945 - Rayno Dwi Adityo (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
As a times and openness, accessibility, mobility information, increase of new perception religion of Islam. No eception for radikalism perception of religion, lead to act of anarchist and terrorism. This view, basically refused the nation ideology of Pancasila and UUD NRI 1945. They call booth of it as thogut and should be combated with war. Their perception it’s verry narrow and not used as well Islamic metodology it self. With analogy and histories approach, this script trying ti find red thread within perception Islamic values inside Pancasila and UUD NRI 1945.